Assessment on Energy Conversion Efficiency and GHG Emissions Rate for Coal, Natural Gas and Biomass Power Plant in Malaysia - Ahmad R.D.R.; Kiong T.S.; Zakaria S.; Abbas A.R.; Phing C.C.; Abdullah K. (Penerbit Akademia Baru, 2023)
Three different power plants have been assessed in terms of energy conversion efficiency and GHGs emission rate. The power plants are coal power plant, natural gas power plant and biomass power plant. The assessments are made by collecting fuels consumption data and generated electricity data of each power plant. In addition to the data collection, observation on operational practices have also been carried out. The energy conversion efficiency and the GHGs emission rate for all power plants are recorded to be lower than the typical values proposed by the literature. The biomass power plant recorded the lowest energy conversion efficiency at 6.47 %. Meanwhile, the natural gas power plant utilizing the combined cycle gas turbine technology recorded the highest overall energy conversion efficiency at 48.35 % and rated to emit GHGs at 0.32 kg CO2e per kWh. 2021. All Rights Reserved.